Biofortified Rocket (Eruca sativa) with Selenium by Using the Nutrient Film Technique - Nascimento, Carolina Seno [UNESP]; Nascimento, Camila Seno [UNESP]; Lopes, Guilherme; Carrasco, Gilda; Gratão, Priscila Lupino [UNESP]; Cecílio Filho, Arthur Bernardes [UNESP] (MDPI, 2022)
Selenium (Se) is an essential micronutrient for humans, but most foods are Se deficient, mainly because of its low content in the soil. A Se-deficient diet results in increased susceptibility to cardiovascular disease, cancer, and hyperthyroidism. Agronomic biofortification is a good alternative to increase Se in food. This study investigated the effect of Se on the growth, yield, and biofortification of the rocket. Plants were grown in a hydroponic system. Seven Se concentrations (0, 10, 20, 30, 40, 50, and 60 µM) were evaluated using sodium selenate. Growth, yield, lipid peroxidation, hydrogen peroxide content, and the enzymatic activity of catalase and ascorbate peroxidase were influenced by the Se concentration. Considering the evaluated parameters, 10–30 µM Se promoted the best results, and with 20 µM, the higher yield. Rocket plants treated with Se in the nutrient solution were biofortified, showing Se contents of 598.96 to 1437.56 mg kg−1 in the dry mass, higher than plants cultivated in a nutrient solution without Se, which presented 167.84 mg kg−1 of Se. Se concentrations of 10–30 µM in the nutrient solution were beneficial for rocket plants, while concentrations above 50 µM were toxic to the plants.
Keywords: malnourishment; Se deficiency; selenate; soilless cultivation; urban agriculture